IDENTIFICATION OF ECONOMIC BEHAVIOR (DISTRIBUTION) IN THE "URANG BANJAR" RIVER CULTURE AS A SUPPLEMENT TO TEACHING MATERIALS IN HIGH SCHOOL - Rahmatullah, Muhammad; Fitri, Fitri; Setiawan, Ananda (International Conference On Social Science Education, 2023)
This research aims to identify and analyse the behaviour of the economic aspects of distribution, showing the rivers of the Banjar people and the role of river utilisation in the economics curriculum of class. The type of research used was qualitative phenomenological, with the research subjects being the Banjarmasin riverside community. This research uses interview and documentation methods with data collection techniques through observation, interviews and documentation. The data analysis technique used is a taxonomic analysis using the Spradley model (Ethnography). The results of the research show that 1) Banjar people still use rivers for distribution activities, 2) Utilization of rivers as distribution activities can be used as a supplement source for local teaching materials in schools, especially in economic learning, 3. There are differences in the use of rivers in the past and present.